Predicting a Suitable Distribution Pattern of Dominant Tree Species in the Northwestern Sichuan Plateau Under Climate Change and Multi-Scenario Evaluation of Carbon Sink Potentials - Wang, Guangjie; Han, Xuemei; Yang, Chen; Qian, Jiangcheng (Frontiers in Environmental Science, 2022)
Climate change threatens the global living environment and afforestation-based carbon sequestration is an effective measure to relieve and adapt to climate changes. In this study, the ideal distribution patterns of Abies, Picea, Quercus and Betula species in forests in Mao County, China were simulated and predicted, respectively, using the maximum entropy niche model, MaxEnt. After, suitable distribution patterns of the four dominant tree species under different scenarios were simulated by overlaying suitable distribution areas for each species. Subsequently, the total carbon sinks of the suitable distribution patterns were estimated by combining the biomass expansion factors (BEF). The optimal scenario for carbon sequestration was found by comparing the total carbon sinks under different scenarios. By comparing the results with existing forest resources in Mao County, the maximum increase of the carbon sink potential was estimated. The results demonstrated that: 1) The MaxEnt model has a good simulation effect and the average AUC of the four tree species is higher than 0.8, indicating that the potential distribution areas of the dominant tree species have relatively high accuracy in the model simulation. 2) The suitable area size order of the four dominant tree species is Picea>Abies>Betula>Quercus. The total suitable area is 295,593.28ha. The order of biomass of the four trees species per unit area is Abies>Betula>Picea>Quercus. 3) When it is suitable to plant multiple tree species simultaneously, the planting combination mode of the trees was chosen according to biomass to obtain maximum carbon reserves. The carbon reserve of this combination mode was 15.81Tg C. 4) Compared with existing forest resources, the maximum carbon reserve potential of the four dominant tree species can increase to 2.13 Tg C in the future. In this study, suitable distribution patterns and carbon sink potentials of the four dominant tree species in the Northwestern Sichuan Plateau were analysed and predicted. The results provide a reference for afforestation plans, tree species selection and regional distribution layouts for future carbon sequestration projects in the plateaus. The study is beneficial for increasing economic benefits and the ecological value of forest carbon sinks in plateaus.